The effect of various field speeds of rice combine harvester on grain loss in Malaysian paddy field / Shamilah Ahmad Mokhtor - Ahmad Mokhtor, Shamilah (Faculty of Plantation and Agrotechnology, 2018)
Rice harvesting has recently become a problem due to labour shortage in Malaysian paddy field. To overcome this problem, about 99.9 % rice fields in Malaysia have been harvested using rice combine harvesters. To this day, the machines are widely used in commercial rice farming in the country. However, the grain loss during rice harvesting in Malaysia is considered quite significant. One of the factors that may have caused the grain loss is the field speed of the combine harvester. Previous researchers have suggested the suitable field speed. Thus, a further study is needed to investigate the connection between current field speeds and grain loss in Malaysia paddy fields. The purpose of the study is to investigate the effect of various field speeds of combine harvester and to find out the most suitable field speed in rice harvesting in order to minimize the grain losses. The finding shows that larger losses occur as the field speed increases. The results also showed that the field speeds has a linear relationship with grain loss, which means the field speed has a significant effect on the grain loss. The best speed was found to be 3.87 km/hr, which cause only 0.67 % grain loss, equalling to RM8.04/ha profit losses. Conclusively, the results can encourage the improvement of mechanization quality in rice harvesting. The outcome of study can directly contribute to reduce rice farmer’s losses.